Unconditioned Stimulus Devaluation Effects in Nutrient-Conditioned Flavor Preferences - Delamater, Andrew R. (2006)
Experiments with different temporal relations between the conditioned stimulus (CS) and the unconditioned stimulus (US) in conditioning assessed whether US devaluation effects can be obtained after nutrient-conditioned flavor preference learning. One flavor (CScarb) was paired with a carbohydrate, Polycose; a 2nd flavor (CSprot) was paired with a protein, casein; and a 3rd flavor (CS−) was presented by itself. Following conditioning, one of the nutrients was devalued through pairings with lithium chloride in the absence of the CS flavors. In a subsequent 2-bottle test, rats preferred CScarb over CSprot; however, this preference was smaller when the carbohydrate was devalued than when the protein was devalued. Results suggest that CS flavors are able to form associations with the sensory features of nutrient USs under a wide variety of circumstances.